The F-theorem in the melonic limit - Benedetti, Dario; Gurǎu, Rǎzvan; Harribey, Sabine; Lettera, Davide (Journal of high energy physics, 2022)
The F-theorem states that in three dimensions the sphere free energy of a field theory must decrease between ultraviolet and infrared fixed points of the renormalization group flow, and it has been proven for unitary conformal field theories (CFTs).
Gesehen am 07.04.2022